СТАБИЛИЗАЦИЯ ПОПУЛЯЦИИ И СЕЛЕКЦИЯ МИКРООРГАНИЗМОВ - ДЕСТРУКТОРОВ ПОЛИЦИКЛИЧЕСКИХ АРОМАТИЧЕСКИХ УГЛЕВОДОРОДОВ (Experimental biology, 2017)
When you use three methods to adapt to the strain of Rhodococcus equi 51KS substrate selection options, as well as the ability to increase in environments with a high content of naphthalene and anthracene.
Keywords: Rhodococcus equi 51KS